ANALISIS PENGARUH KUALITAS PRODUK, LAYANAN PENUNJANG DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN DALAM MEMBELI SEPEDA MOTOR (Studi Pada Pengguna Sepeda Motor Kawasaki Ninja di Semarang) - Riyan Tri Asmoro, 11.05.51.0061; Sutejo, Bambang (Students Journal of Economic and Management, 2015)
This research takes the object of respondents on Kawasaki Ninja Siliwangi Semarang Dealer. The reason of choosing the object of the research based on the up and down purchases on the Dealer, and may be indicated that there is competition in sport motorcycle. From that phenomenon then it is necessary to proof and study to analyze the influences of the Product Quality, the Service Support and the Brand Image to Consumer Statisfication. The sampling method uses purposive sampling with the period of research on 24 June 2015 until 24 July 2015 and takes 100 rteespondents. The relationship and or influence between variables are explained using linear regression method and determination coefficient and hypotheses test using t test and F test. The result of this shows the product quality, the service quality and the brand image influence positive significant to the consumer statisfication. Keywords:Product quality, service support, brand image and consumer statisfication.